Rhinovirus Detection in the Nasopharynx of Children Undergoing Cardiac Surgery Is Not Associated With Longer PICU Length of Stay: Results of the Impact of Rhinovirus Infection After Cardiac Surgery in Kids (RISK) Study. Issue 1 (7th October 2020) - Roeleveld, Peter Paul; Van Rijn, Anneloes L.; de Wilde, Rob B. P.; van Zwet, Erik W.; Wink, Jeroen; Rozendaal, Lieke; Hogenbirk, Karin; Hazekamp, Mark G.; Man, Wing Ho; Sidorov, Igor; Kraakman, Margriet E. M.; Claas, Eric C. J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To determine whether children with asymptomatic carriage of rhinovirus in the nasopharynx before elective cardiac surgery have an increased risk of prolonged PICU length of stay. Study Design: Prospective, single-center, blinded observational cohort study. Setting: PICU in a tertiary hospital in The Netherlands. Patients: Children under 12 years old undergoing elective cardiac surgery were enrolled in the study after informed consent of the parents/guardians. Interventions: The parents/guardians filled out a questionnaire regarding respiratory symptoms. On the day of the operation, a nasopharyngeal swab was obtained. Clinical data were collected during PICU admission, and PICU/hospital length of stay were reported. If a patient was still intubated 3 days after operation, an additional nasopharyngeal swab was collected. Nasopharyngeal swabs were tested for rhinovirus and other respiratory viruses with polymerase chain reaction. Measurements and Main RESULTS: Of the 163 included children, 74 (45%) tested rhinovirus positive. Rhinovirus-positive patients did not have a prolonged PICU length of stay (median 2 d each; p = 0.257). Rhinovirus-positive patients had a significantly shorter median hospital length of stay compared with rhinovirus-negative patients (8 vs 9 d, respectively; p = 0.006). Overall, 97 of the patients (60%) tested positive for one or more respiratory virus. Virus-positive patients had significantly shorter PICU and hospital length of stay, ventilatory support, and nonmechanical ventilation. Virus-negative patients had respiratory symptoms suspected for a respiratory infection more often. In 31% of the children, the parents reported mild upper respiratory complaints a day prior to the cardiac surgery, this was associated with postextubation stridor, but no other clinical outcome measures. Conclusions: Preoperative rhinovirus polymerase chain reaction positivity is not associated with prolonged PICU length of stay. Our findings do not support the use of routine polymerase chain reaction testing for respiratory viruses in asymptomatic children admitted for elective cardiac surgery.